Hydration Literacy and Fluid Intake Among Older Persons with Chronic Diseases - Anuja, Mantana; Rhiantong, Jittawadee; Panuthai, Sirirat (Nursing Journal CMU, 2024)
Hydration literacy can help older persons with chronic diseases analyze their own daily water consumption. They can also make decisions to increase or decrease their daily water intake to maintain an appropriate level for their health condition. This descriptive correlation research aimed to describe hydration literacy, fluid intake, and the association between hydration literacy and fluid intake among older persons with chronic diseases. The participants consisted of 213 older persons with chronic diseases who received healthcare service from sub-district Health Promotion Hospitals in Mueang Lamphun district, Lamphun province. The participants were selected using proportional stratified random sampling. The research tools included a demographic and illness data recording form, a water intake record form, and a hydration literacy interview measurement. The hydration literacy interview measurement was tested for reliability, and an acceptable coefficient of .93 was obtained. Data were analyzed using descriptive statistics and Pearson's correlation coefficient. The results showed that the older persons with chronic diseases had a moderate level of hydration literacy. The average daily fluid intake was 2,413.97 milliliters (SD = 760.69), which was above the standard criteria. Hydration literacy had a significant positive correlation with fluid intake (r = .514, p < .01). The results of this research can be used as information for healthcare professionals involved in caring for older persons with chronic diseases, in promoting hydration literacy and fluid intake among this population.